Acoustic and Electroglottographic Characteristics Associated with Tracheoesophageal Speech of Cantonese - Manwa Lawrence Ng; Nan Yan; Kalai Nana Chiu; Yang Chen (康复学报)
The present study examined the acoustic and neoglottal area characteristics of tracheoesophageal (TE) speech of Cantonese. Seven TE speakers and seven age-matched laryngeal (NL) speakers produced sustained vowels and passage reading. Both acoustic and electroglottographic (EGG) signals were recorded and analyzed using Praat and Voce Vista. Results indicated that TE speech was associated with a significantly lower fundamental frequency (F0) than NL speech in passage reading. Expectedly, significantly higher jitter, shimmer and closed quotient (SQ), lower harmonic-to-noise ratio (H/N) values, as well as higher formant frequencies in sustained/i/phonation were found for TE speech in both sustained vowel phonation and passage reading. The findings may explain the perceived hoarse, breathy and low-pitch voice of TE speech. Results were discussed in terms of higher sound source position, greater tissue density, slower movement during closing phase and a periodic vibration of neoglottis of TE speakers than the vocal folds of NL speakers.